MOST PORBABLE PRODUCING ABILITY (MPPA) OF DAIlY MILK PRODUCTION FOR LOCAL COWS - Raoof, S.O. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This research was carried out on 51 local raised in three local cow herds in Erbil plain, for the period from 2016 to 2017.  To estimate the most probable producing ability (MPPA) of cows and to study the effect of non-genetic factors affecting on daily milk production (DMP) and to estimate the repeatability for (DMP). The most probable producing ability (MPPA) of local cows was calculated by using the test day records and then the animals were ranked based on their MPPA values. Cow number 1237 inquired the highest value of MPPA (16.91 kg) for DMP among all tested cows in the three flocks. The overall mean for the (DMP) was 11.85 kg. The results of current study revealed that the effect of flock, parity, season of calving, services per conception and dry period length (days) had a significant effect (p